Activity Profiles and Physiological Responses of Representative Tag Football Players in Relation to Playing Position and Physical Fitness. - Luke W Hogarth; Brendan J Burkett; Mark R McKean (PLoS ONE, 2015)
This study determined the physical fitness, match-activity profiles and physiological responses of representative tag football players and examined the relationship between physical fitness and the match-activity profile. Microtechnology devices and heart rate (HR) chest straps were used to determine the match-activity profiles of sixteen tag football players for five matches during the 2014 Australian National Championships. The relationships between lower body muscular power, straight line running speed and Yo-Yo intermittent recovery test level 2 (Yo-Yo IR2) and the match-activity profile were examined using Pearson's correlation coefficients. Outside players had greater lower body muscular power (ES = 0.98) and straight line running speed (ES = 1.03-1.18) than inside players, and also covered greater very high-speed running (VHSR) distance/min (ES = 0.67) and reached higher peak running speeds (ES = 0.95) during matches. Inside and outside players performed a similar number of repeated high-intensity effort (RHIE) bouts and reported similar mean and maximum efforts per RHIE bout. However, there were differences between playing positions for mean and maximal RHIE effort durations (ES = 0.69-1.15) and mean RHIE bout recovery (ES = 0.56). Inside and outside players also reported small to moderate differences (ES = 0.43-0.80) for times spent in each HR zone. There were a number of moderate to very large correlations between physical fitness measures and match-activity profile variables. This study found lower body muscular power, straight line running speed and Yo-Yo IR2 to be related to the match-activities of representative tag football players, although differences between inside and outside players suggest that athlete testing and training practices should be modified for different playing positions.